2008
DOI: 10.1111/j.1365-2982.2008.01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in the neurochemical coding of the myenteric plexus of the human colon and changes in patients with slow transit constipation

Abstract: There are differences in the structure and function between regions of the colon. In patients with slow transit constipation the activity of all regions is markedly slowed. Counts of colonic neurones in slow transit constipation have been semiquantitative and led to varying results. We have applied new methods of quantification of markers in whole mounts of the colonic myenteric plexus to compare density of innervation between regions and between normal patients and those undergoing resection for severe consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
76
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 49 publications
13
76
2
Order By: Relevance
“…Conversely, increased NO synthase-positive neurons and activities are associated with STC (Tomita et al, 2002;Wattchow et al, 2008). Our result is in agreement with the study by Mitolo-Chieppa et al (2001) performed in male STC circular muscle, which shows that EFS-induced relaxation of SP-precontracted muscle strips is reduced at 0.5 Hz (ATP mediated) and enhanced at 4 Hz (NO) medicated compared with control, suggesting an abnormality in NO and ATP release.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Conversely, increased NO synthase-positive neurons and activities are associated with STC (Tomita et al, 2002;Wattchow et al, 2008). Our result is in agreement with the study by Mitolo-Chieppa et al (2001) performed in male STC circular muscle, which shows that EFS-induced relaxation of SP-precontracted muscle strips is reduced at 0.5 Hz (ATP mediated) and enhanced at 4 Hz (NO) medicated compared with control, suggesting an abnormality in NO and ATP release.…”
Section: Discussionsupporting
confidence: 82%
“…3 H]ACh in response to EFS in STC taenia coli muscle strips and decreased choline acetyltransferase in colonic myenteric neurons of STC have been demonstrated (Burleigh, 1988;Wattchow et al, 2008). Conversely, increased NO synthase-positive neurons and activities are associated with STC (Tomita et al, 2002;Wattchow et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that the interval between CMCs is reduced in the transverse colon and splenic flexure (9). Other studies have demonstrated reductions in specific neurochemical classes of myenteric neurons in STC patients (4,15,21,32), in addition to reduced density of pacemaker cells (16) or specific types of neuromuscular transmission (31). Whether anatomical or functional changes in the large intestine of STC patients represents a cause or an effect of STC is not fully clear.…”
mentioning
confidence: 99%
“…Moreover adecrease in cholineacetyltransferasepositive neurons and arelative increase in the percentage of nitric oxide synthase positive neurons have been demonstrated in middle-aged aged adults suffering from slow-transit constipation (Wattchow et al, 2008). However, a reduction in myenteric neuronal number is also seen in humans with no detectable GI disorders and therefore their involvement in age-related constipation is questionable (Bernard et al, 2009).…”
Section: Introductionmentioning
confidence: 99%